STRATEGI KOSMONITA MALANG UNTUK MENGOPTIMALISASI KONTEN PROGRAM PEREMPUAN DALAM MEMPERTAHANKAN POSITIONING SEBAGAI RADIO BERSEGMEN PEREMPUAN - Sylvatri, Hapsari Dian; Safitri, Reza; Wulandari, Maulina Pia (Jurnal Nomosleca, 2019)
Abstract This study aims to optimize the content of women's programs in the form of inserts on Kosmonita radio Malang. This research is an action research study, that focuses on actions that involve researchers and community members, organizations that want to be studied. The purpose of action research is to produce changes with certain actions to refer to social change. The object of this research is Radio Kosmonita Malang, and focuses on radio marketing strategy theory by using STP theory (segmentation, targeting, positioning) and also using SWOT analysis (Strength, Weakness, Opportunity, and Thread) as supporting theories in order to find the right strategy to optimize women's content programs in Kosmonita radio Malang. Data collection was conducted with Focus Group Discussion, interviews, making radio inserts, and conducting surveys on Kosmonita radioâ€™s listeners in Malang. The results showed that before there was an insert, the inspiring woman program was not optimal, but after the insert, there was an optimization of women's program content. The conclusion of this study is the addition of inspiring women's content, which contains the success stories of female in various fields, increasingly optimizing this program. Based on these conclusions, the researchers suggested to mak the insert as a talk show program that broadcast regularly on Kosmonita radio Malang and the second is regular research or survey so that it could provide new innovations for broadcast programs on Kosmonita radio Malang. Keywords: radio, marketing strategy, swot analysis, action research.DOI :Â https://doi.org/10.26905/nomosleca.v5i1.2784